Peningkatan Kemampuan Pemecahan Masalah Matematika Peserta Didik Kelas IV Materi Bangun Datar Melalui Model Pembelajaran Problem Based Learning - Rofisian, Nela; Lestari, Sri; Rozana, Etika; Cahyaningtyas, Fadlilah; Amanda, Fara Maulina; Maulidina, Farras Kurnia; Utami, Fatin Nur; Purwanti, Febri (Universitas Muhammadiyah Magelang, 2025)
This study aims to improve the mathematical problem solving ability of fourth grade students on flat building material through the application of the Problem Based Learning (PBL) learning model. The problem experienced by fourth grade students of SDN 1 Karanganom is experiencing difficulties in understanding the basic concepts of flat shapes such as area, perimeter, and their properties. This difficulty can be seen from the evaluation results which show that most students experience errors in solving problem solving problems related to flat shapes. This study used a class action research method (PTK) with a subject of 19 students in class IV SDN 1 Karanganom in the 2024-2025 academic year which was carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection. Through data sources, namely quantitative data with observation, test and documentation data collection techniques. Data were obtained through math problem solving ability tests and observation of the learning process. The results showed an increase in the mathematical problem solving ability of fourth grade students on flat building material through the Problem Based Learning learning model, in cycle I with students who completed the KKM as much as 42.10%. While in cycle II there was an increase of 84.21% who had reached KKM.